Neuro-what? Which neuroscience products should you take seriously?. Issue 4 (1st July 2019) - Merzenich, Michael
Abstract : Purpose: Discovery in the field of neuroscience is rapid and keeping pace can be overwhelming. This paper aims to summarize the history of how the field has developed and provides seven key questions you should ask when assessing the validity of "neuro" products and services. Design/methodology/approach: This paper is based on the author's five decades of experience as a neuroscientist. Findings: Developments in neuroscience can assist organizations to deliver more effective OD and learning and development (L&D) interventions. It is, however, critical to identify well-researched and evidenced products and services. Originality/value: Neuroscience is developing at a high speed our understanding of the brain. This paper provides L&D professionals with a set of principles on which to assess the voracity of what they are offered, to sort the wheat from the chaff.